Comparison of the Effectiveness of Different Barrier Enclosure Techniques in Protection of Healthcare Workers During Tracheal Intubation and Extubation. Issue 8 (June 2020) - Ibrahim, Mohamed; Khan, Ejaz; Babazade, Rovnat; Simon, Michelle; Vadhera, Rakesh
Abstract : The coronavirus disease 2019 (COVID-19; SARS-CoV-2) pandemic has created serious challenges to anesthesiologists. As hospitalized patients' respiratory function deteriorates, many will require endotracheal intubation. Airway management of infected patients risks aerosolization of viral-loaded droplets that pose serious hazards to the anesthesiologist and all health care personnel present. The addition of an enclosure barrier during airway management minimizes the hazard by entrapping the droplets and possibly the aerosols within an enclosed space adding additional protection for health care workers. The aim of this study was to compare the effectiveness of different barrier enclosure techniques during tracheal intubation and extubation. Abstract : Supplemental Digital Content is available in the text.